In vitro evaluation of three different biomaterials as scaffolds for canine mesenchymal stem cells - Pereira-Junior, Oduvaldo Câmara Marques; Rahal, Sheila Canevese [UNESP]; Lima-Neto, João Ferreira; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Monteiro, Frederico Ozanan Barros (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To evaluate in vitro ability the of three different biomaterials - purified hydroxyapatite, demineralized bone matrix and castor oil-based polyurethane - as biocompatible 3D scaffolds for canine bone marrow mesenchymal stem cell (MSC) intending bone tissue engineering. METHODS: MSCs were isolated from canine bone marrow, characterized and cultivated for seven days with the biomaterials. Cell proliferation and adhesion to the biomaterial surface were evaluated by scanning electron microscopy while differentiation into osteogenic lineage was evaluated by Alizarin Red staining and Sp7/Osterix surface antibody marker. RESULTS: The biomaterials allowed cellular growth, attachment and proliferation. Osteogenic differentiation occurred in the presence of hydroxyapatite, and matrix deposition commenced in the presence of the castor oil-based polyurethane. CONCLUSION: All the tested biomaterials may be used as mesenchymal stem cell scaffolds in cell-based orthopedic reconstructive therapy.
Keywords: Hydroxyapatites; Bone Matrix; Castor Oil; Polyurethanes; Stem Cells